Recent considerations in regenerative endodontic treatment approaches - Hacer Aksel; Ahmet Serper (Elsevier, 2014)
Background/purpose: Regenerative approaches in endodontics are considered in two concepts. One is a revascularization approach to achieve continued apical formation while the other involves the pulp/dentin regeneration via tissue engineering technology. Recently, some case reports have shown that infected immature teeth can be treated by revascularization approach. However, there is still no standardized treatment protocol for this procedure. The purpose of this review article was to evaluate the effects of regenerative endodontic treatment for necrotic immature permanent teeth and to discuss recent treatment approaches. Materials and methods: Articles published in dental journals from January 2001 to August 2013 were searched using the following keywords: immature permanent teeth OR immature teeth OR pulp revascularization OR pulp revitalization OR regenerative endodontics by using electronic databases (MEDLINE using the PubMed search engine, Embase, Scopus, and Cochrane Central Register of Controlled Trials). Results: The regenerative endodontic treatments with various methods and materials result in a significant increase in root length and dentinal wall thickness. Stimulation of stem cells in apical root canal system is required to induce tissue formation and continued root development. Alternative disinfection materials and protocols are required. Conclusion: Although the regenerative treatment approaches have good clinical outcomes in the majority of case reports, the outcomes are unpredictable. Since the current clinical protocols for regenerative endodontics do not fully fulfill the triad of tissue engineering ((growth factors, scaffold and stem cells), further translational studies are required to achieve more pulp- and dentin-like tissue in the root canal system to achieve pulp regeneration.